Postoperative Opioid-induced Respiratory Depression. Issue 1 (March 2016) - Lee, L.A.; Caplan, R.A.; Stephens, L.S.; Posner, K.L.; Terman, G.W.; Voepel-Lewis, T.; Domino, K.B.
Abstract : ( Anesthesiology. 2015; 122:659–665) Postoperative opioid-induced respiratory depression can cause brain damage and death in the perioperative period. The Joint Commission, the Institute for Safe Medication Practices, and the Anesthesia Patient Safety Foundation all suggest that the negative outcomes related to respiratory depression are preventable.